Analisis Cacat Produk Dimensi Diameter Snap Tidak Standar pada Botol 100 ml Berbahan Dasar High-Density Polyethylene (HDPE) - Achmad Afiq Ananda Putra; Widia Setiawan; Braam Delfian Prihadianto; Galuh Bahari (Proklamasi 45 University, 2025)
Extrusion blow molding is a process used to form plastic bottles, with High-Density Polyethylene (HDPE) being the most commonly used material. A defect in the snap diameter that did not meet the standard was identified during the production of 100 ml bottles at PT X Jakarta, potentially reducing product quality and affecting its functionality. This study aims to identify the root causes of this defect and propose corrective actions and improvements to enhance product quality. The methodology includes using a Fishbone Diagram to determine the root causes, applying the 5W+1H analysis to develop corrective action proposals, and implementing the Poka-Yoke method as an improvement strategy. The findings indicate that the defects are caused by three main factors: human, method, and machine. Human-related factors include a lack of operator understanding of quality standards, insufficient training, and a limited number of technicians. Method-related factors involve inadequate maintenance and improper bottle handling, while machine-related factors include mold dimension changes, dirty die heads, and the need for machining parameter adjustments. The proposed corrective actions for human factors involve regular training, the provision of Standard Operating Procedures (SOPs), visual guidelines, and additional technicians. Machine-related improvements include periodic inspections, die head cleaning, and machining parameter testing, while method-related improvements focus on scheduled preventive maintenance and proper bottle runner arrangement. Further improvements involve implementing the Poka-Yoke method by installing an alarm siren that activates when air compressor pressure falls below the standard and adding markings to help operators better understand machine parameters during production.